A highly reliable physics-based SPICE compact model of IGZO memristor considering the dependence on electrode metals and deposition sequence. (April 2020) - Jang, Jun Tae; Min, Jungi; Kim, Donguk; Park, Jingyu; Choi, Sung-Jin; Kim, Dong Myong; Cho, Seongjae; Kim, Dae Hwan
Highlight: The highly accurate and realistic SPICE compact model for an IGZO-based memristor has been developed. The switching layer is IGZO and the electrode metals are Pd and Mo, on the Si substrate. The switching behaviors of the IGZO memristor have dependence on the order of electrode processes. The interface property is significantly altered over the sputtering on the bottom electrode. We are not able to observe the symmetric I - V curves even when those two electrodes exchange their positions. Abstract: In this work, a SPICE compact model of indium-gallium-zinc oxide (IGZO) memristor in consideration of IGZO and electrode materials having non-quasi-statically updated Schottky barrier heights has been developed. In order for compact modeling of an analog memristor with higher accuracy, understanding of its switching characteristics and conduction behaviors needs to be preceded. It has been empirically revealed that they are dependent on metal species of the electrodes and processing approach. The switching characteristics are more weightedly determined by the interface between the switching layer and the metal with lower workfunction out of two electrode metals and interface status has been controlled by an Ar bombardment in this work. In order for identifying the conduction mechanism, a series of device simulations have been performed and the internal electric field distribution over the device structure has been closely investigated. It has been shown that the conduction behaviors are mainly determined by the thermionic emission taking place between Pd electrode and IGZO switching layer. For preparing the model parameters, along with the experimental results, transient measurement techniques have been cultivated at the same time, which has made possible to tell the difference between sets of model parameters obtained by theory and the techniques. In consequence, a highly reliable physics-based modeling for IGZO memristor has been developed through identification of switching and conduction mechanisms and extraction of the model parameters with the simultaneous help of Verilog-A equation build-up, which has demonstrated a plausible agreement with the measurement results.